2022
DOI: 10.1038/s41531-022-00333-8
|View full text |Cite
|
Sign up to set email alerts
|

DAT and TH expression marks human Parkinson’s disease in peripheral immune cells

Abstract: Parkinson’s disease (PD) is marked by a loss of dopamine neurons, decreased dopamine transporter (DAT) and tyrosine hydroxylase (TH) expression. However, this validation approach cannot be used for diagnostic, drug effectiveness or investigational purposes in human patients because midbrain tissue is accessible postmortem. PD pathology affects both the central nervous and peripheral immune systems. Therefore, we immunophenotyped blood samples of PD patients for the presence of myeloid derived suppressor cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 201 publications
6
48
0
Order By: Relevance
“…We demonstrated that peripheral immune cells display an association with human PD. 124 The role of neuroinflammation in the pathogenesis of PD is clear, with elevated levels of proinflammatory mediators in the basal ganglia and cerebrospinal fluid of PD patients. Furthermore, reducing inflammation (a major therapeutic target of IBD therapy) may reduce the risk of developing PD, suggesting a different biological effect.…”
Section: Future Directions and Researchmentioning
confidence: 99%
“…We demonstrated that peripheral immune cells display an association with human PD. 124 The role of neuroinflammation in the pathogenesis of PD is clear, with elevated levels of proinflammatory mediators in the basal ganglia and cerebrospinal fluid of PD patients. Furthermore, reducing inflammation (a major therapeutic target of IBD therapy) may reduce the risk of developing PD, suggesting a different biological effect.…”
Section: Future Directions and Researchmentioning
confidence: 99%
“…101 Interestingly, same as TH expression in monocytes, 130 DAT expression in PBMCs from PD patients was also found to be increased. 131 Experimental evidence shows DA can modulate inflammation through redox pathways and the generation of reactive oxygen metabolites, such as DA quinone (DAQ). 98,153,154 For example, DA can reduce NO and iNOS production, TNF-a, IL-1b and IL-6 expression in the presence of tyrosinase, which catalyses the oxidation of DA to DAQ in both murine primary and microglial BV-2 cell line 98,153 (Table 1).…”
Section: Dr-independent Mechanismsmentioning
confidence: 99%
“…131 The treatments also affect the expression patterns of DAT and TH as L-dopa/benserazide treatment in mice restored baseline levels of both DAT and TH, whereas L-dopa alone only restored TH expression on PBMC. 131 Besides their effects on immune regulation in the periphery, L-dopa also contributes to glial neuroinflammatory responses and long-term therapy side-effects, including LID. 188,189 The exact mechanism that causes LID and other motor complications has yet to be defined but increasing preclinical evidence suggests that glial cells are potential contributors.…”
Section: Immune Regulatory Effects Of Dopaminergic Antiparkinsonian D...mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this fact, the utilisation of TH as a biomarker of PD was investigated in a few studies several decades ago. Recent studies unexpectedly revealed that monocytes isolated from blood of PD patients express significantly higher levels of TH in comparison to age-matched healthy controls (38). It was suggested that the dopaminergic machinery on peripheral immune cells displays an association with human PD, with some implications in facilitating diagnosis.…”
Section: Tyrosine Hydroxylasementioning
confidence: 99%